QUALITY BY DESIGN BASED DISSOLUTION TEST DEVELOPMENT OF OMEPRAZOLE EXTENDED RELEASE FORMULATION - MANRANJAN, VAYEDA CHINTAN; Yadav, Devendra Singh; Jogia, Hitesh Amrutlal (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Objective: The objective of the current work is to develop dissolution method for the formulation contains mix pellets of omeprazole delayed release (DR) and extended release. Methods: The dissolution method design was based on the quality by design principles, the selection of dissolution media, apparatus and drug release specification was based on scientific understanding of drug release mechanism and stability of omeprazole. Design of experiments (DOE) employed to assess the huskiness of the dissolution test using pH, volume of media and concentration of surfactant as critical test parameters. Results: Omeprazole DDR formulation shows more than 85% cumulative drug release at 105 minutes with the % RSD less than 5 among six units. Based on p values (<0.1) of Shapiro-Wilk test for normality, Response-1 and 2 are statistically analysed with ANOVA statistics. The ANOVA analysis shows significant effect of ‘volume' and ‘pH' of dissolution media (p<0.05) on Quality Target Test Profile. Conclusion: The outcome of DOE assessed with 95% confidence interval ANOVA statistics, which reveals that the dissolution test is rugged and can be used for routine quality control test of omeprazole dual DR formulation. Keywords: Dissolution, Development, Omeprazole, Quality by design, Design of experiments, ANOVA.